2013
DOI: 10.1097/npt.0b013e318283de0d
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor Training and Neural Reorganization After Stroke

Abstract: Background and Purpose Impaired hand function decreases quality of life after stroke. The purpose of this study was to pilot a novel two-week upper extremity sensorimotor training program. This case series describes the training program and highlights outcome measures used for documenting behavioral change and neural reorganization. Case Description Sensorimotor evaluation identified behavioral changes, activity induced neural reorganization was examined using sensory fMRI, diffusion tensor tractography, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 82 publications
(88 reference statements)
2
43
0
Order By: Relevance
“…11 Three trials were the ones that demonstrated the ability of somatosensory interventions to cause functional recovery on stroke survivors by triggering cortical reorganization -a total of 17 out of 23 patients. [12][13][14] This possibly validates the theory that recovery depends on cortical circuits which receive the appropriate sensory input from the periphery and reconnect the partially disconnected circuits in order to 'rescue' the repair of the circuits and not 'collapse' the lesioned circuits which would otherwise be the case. Therefore, the therapist offers guided or assisted recovery through perceptual inputs based on bottom-up targeted stimulation.…”
Section: Resultssupporting
confidence: 67%
“…11 Three trials were the ones that demonstrated the ability of somatosensory interventions to cause functional recovery on stroke survivors by triggering cortical reorganization -a total of 17 out of 23 patients. [12][13][14] This possibly validates the theory that recovery depends on cortical circuits which receive the appropriate sensory input from the periphery and reconnect the partially disconnected circuits in order to 'rescue' the repair of the circuits and not 'collapse' the lesioned circuits which would otherwise be the case. Therefore, the therapist offers guided or assisted recovery through perceptual inputs based on bottom-up targeted stimulation.…”
Section: Resultssupporting
confidence: 67%
“…After 60 seconds, the beads that had been moved to the other side of the box were counted (7,8). A reliability test retesting these tools was conducted in patients with stroke (results: 0.97 -0.89) (6).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies implemented similar interventions of somatosensory stimulation. Sensorimotor training improved the functional recovery of 2 chronic stroke survivors in a 2-week intervention with neural reorganization being induced [45]. Moreover, a program of stretching, range of motion exercises, and soft tissue mobilization techniques offered to 5 chronic stroke patients in a 3-week intervention managed to provide functional improvement along with cortical reorganization [46].…”
Section: Discussionmentioning
confidence: 99%